Cultura financiera y su relación con el nivel de endeudamiento de los comerciantes del Mercado Campo Ferial de Contamana, año 2023 - Menendez Flores, Elcita Patricia (2024)
The objective of this report was to determine the relationship between financial culture and the level of indebtedness of the merchants of the Contamana fairground market, year 2023. Where it was decided to use an applied type of research, descriptive and correlational level with a non-experimental design. taking as a population 100 merchants who were used a survey to collect information. According to the results obtained, the financial culture of the merchants is rated as average (31%); while the level of indebtedness of merchants is regular by (28%). Determining that there is a positive and significant relationship between variables, contrasted by a coefficient of 0.823 and a significance of 0.000. the same for the financial knowledge dimension (r=0.788; p=0.000) for financial planning (r=0.796; p=0.000) and financial control (r=0.785; p=0.000), both dimensions are significantly related to the variable debt level.